Characteristics and Outcome of Hospitalized Children with COVID-19: A Single Center Experience - Nabeeha N. Akram (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objectives: Are to describe the clinical, and laboratory features of patients hospitalized with COVID-19 and to compare some of these parameters between patients with and without MIS-C.Methods: A cross sectional study, undertaken over a 10 months period from 1st of march to 31 of December 2020 at child’s central teaching hospital in Baghdad city , Iraq.Results: In total, 80 children hospitalized with a diagnosis of COVID-19. The mean age of the patients was 6.05±5.1years.60% were male and 46.35% had no comorbidities . Different types of malignancies were the most common comorbidity accounting for 22.5% of the patients. A history of contact with infected person was reported in 27.5% of the patients. Chest X-ray revealed that 52.5% of the patients had normal findings. 11.25% developed multi systemic inflammatory syndrome. Only two hematological abnormalities were significant in pediatric COVID-19 cases for development of MIS-C which is elevated NLR and CRP. In this study, there were no deaths linked to COVID-19 admission..Conclusions : The majority of children admitted to the hospital with confirmed COVID-19 have a mild course and a good outcome. malignancy is the commonest comorbidity associated with COVID-19 admissions. Elevated Neutrophil: lymphocyte ratio and CRP are independently associated with development of MIS-C in pediatric COVID-19.